Captive breeding of Oncorhynchus myskiss, a threatened and endemic species to the Western Ghats, India- A conservatory aspect - Venkatachalam Ramasubramanian1; Karthik Ganesh2, Venkatachalam Uthayakumar1* (International Multidisciplinary Research Journal, 2011)
A comparative study on the reproductive performance of Oncorhynchus myskiss, two different doses of Ovaprim and Luteinizing-hormone-releasing hormone (LHRH) was conducted. Different doses of Ovaprim ranging from0.60 to 2.05ml/kg for male fishes and 2.05 to 2.50ml/kg for female fishes was injected. 0.0310 to 0.355 ml LHRH/kg and 0.0640 to 0.0730 ml LHRH/kg was administrated to male and female fishes respectively. The egg production, deformatities and survival rates were observed for all treatments. All the observed values were tabulated and statistically analyzed. The maximum hatchability rate percentage of Ovaprim was at the dose of 2.40ml/kg (84Â±0.640) where as LHRH showed maximum performance at 0.0710 ml/kg dose (85Â±0.750). The outcome of this study can be effectively used for the captive breeding and conservation of Rainbow trout, O. myskiss an endangered cold water fish of Western Ghats, India.